PENGARUH LITERASI DIGITAL DAN KEMANDIRIAN BELAJAR TERHADAP MOTIVASI BELAJAR MAHASISWA PENDIDIKAN EKONOMI STAMBUK 2020 - Usli, Vera Afriani (Universitas Dharmawangsa, 2022)
The problem in this study is that Economics Educations students in stambuk 2020 do not yet have high learning motivation, which is indicated by the presence of students who are less active and concentrated when studying, lack curiosity and enthusiasm, and lack confidence in their abilities. The purpose of this study was to determine the effect of digital literacy and learning independence on the learning motivation of students in Economics Education Stambuk 2020. Sampling using the Probability Sampling method with the Simple Random Sampling technique. Determining the number of samples using the Slovin formula obtained a sample of 70 students. The data analysis technique used is multiple linear regression analysis, partial hypothesis testing, simultaneous hypothesis testing, and the coefficient of determination test. The results showed: (1) Multiple linear regression equation Y=14,210+0,371X1+0,272X2+e; (2) Partially Digital Literacy (X1) has a positive effect and significant on Learning Motivation (Y) of Economic Education Student in Stambuk 2020; (3) Partially Independent Learning (X2) has a positive effect and significant on Learning Motivation (Y) of Economic Education Student in Stambuk 2020; (4) Simultaneously Digital Literacy (X1) and Learning Independence (X2) has a positive effect and significant on Learning Motivation (Y) of Economic Education Student in Stambuk 2020, with (5) a Contribution of 36,6%.